Prebiotics, their effect in patients with gastrointestinal diseases. - Rojas-Renjifo, Katerine (2022)
Background: gastrointestinal diseases GID occur due to morphological and physiological irregularities, affecting the intestinal flora. In the scientific literature, it is reported that, through in vivo and in vitro studies, prebiotics can help improve some of these symptoms, reducing the time of involvement and/or avoiding contracting the disease. Aim: The effects of prebiotics in patients suffering from GID, mainly diarrhea, are described through scientific evidence. Materials and methods: A search was carried out in various databases using Boolean operators and the structuring of search equations combining health descriptors. Of the articles identified, those that met the inclusion criteria were selected. Results: The prebiotics FOS, GOS, and FOS/GOS were found to have the best impact on the recovery of patients with GID since they allow better development of the intestinal microbiota and fulfill various functions, for example, the intestinal barrier. Conclusion: The prebiotics, with the most significant scientific evidence reported in the literature, that allow better development of the intestinal microbiota are FOS, GOS, and Inulin. Prebiotics can reduce morbidity and survival of intestinal microbiota after infections of rotavirus, Salmonella, E. coli, and others. However, no specific recommendations were found in the scientific literature for using prebiotics to manage the diarrheal disease.